Android Application as an Innovative Learning Media: Increasing Students' Historical Empathy Through the History of the Balinese Kingdom - I Made Devid Krisna Utama Putra; Muhammad Akhyar; Akhmad Arif Musadad (LPPM Undiksha, 2024)
The lack of digital learning media makes it difficult for students to study anywhere. This research aims to analyze Android-based media applications for the history of the Balinese Kingdom that are suitable for learning media for class X high school Hindu and Buddhist Kingdoms material. This research method is research and development (R&D) with a 4-D approach. The subject of this research is class X SMA. The validation process involves experts in the field of materials and media. Data collection methods through interviews, surveys, questionnaires and literature studies. The data analysis technique uses quantitative descriptive analysis. The research results show that the Android-based media application for the history of the Balinese kingdom based on Hindu and Buddhist kingdom material is very suitable for use as an alternative learning media to increase historical empathy. By using augmented reality (AR) technology, students can explore historical sites in realistic 3D, allowing them to experience the atmosphere of the past more realistically. Learning media using Android-based applications can provide a more exciting and relevant approach for students, increase historical empathy, and expand the accessibility of learning materials. This research implies that the use of technology such as augmented reality (AR) and multimedia interaction makes historical material more exciting and easier to understand and allows students to engage emotionally and deeply with the material being studied.